TRANSPORT AND SUBSTANTIAL DEVELOPMENT - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Transport and mobility are essential preconditions for sustainable development. Transport affects social, economic and environmental sustainability. Environmental sustainability is affected negatively by transport through the consumption of non renewable energy, the emission of harmful pollutants and greenhouse gases.Sustainable transport is safe, high quality and accessible to all, ecologically sound, economically viable and positive contributor to local, national and international development.Integrated urban and rural transport planning, as welllas supportive fiscal and regulatory policies, combined with the development of new technologies and greater international cooperation , are key factors for a chieving a transport sector that meets the requirements of sustainable development.